2015
DOI: 10.1021/acsami.5b01423
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Polymer Architecture on the Structural and Biophysical Properties of PEG–PLA Nanoparticles

Abstract: Polymers made of poly(ethylene glycol) chains grafted to poly(lactic acid) chains (PEG-g-PLA) were used to produce stealth drug nanocarriers. A library of comblike PEG-g-PLA polymers with different PEG grafting densities was prepared in order to obtain nanocarriers with dense PEG brushes at their surface, stability in suspension, and resistance to protein adsorption. The structural properties of nanoparticles (NPs) produced from these polymers by a surfactant-free method were assessed by dynamic light scatteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 51 publications
2
56
0
Order By: Relevance
“…S11-S14, ESI †). 13 Overall, these results are consistent with nanoparticles exhibiting a solid-like PLA core, stabilized by a solubilized PEG corona. 40 The use of an external standard (methanol) allowed for quantification of PEG on nanoparticle surfaces relative to the total PEG content.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…S11-S14, ESI †). 13 Overall, these results are consistent with nanoparticles exhibiting a solid-like PLA core, stabilized by a solubilized PEG corona. 40 The use of an external standard (methanol) allowed for quantification of PEG on nanoparticle surfaces relative to the total PEG content.…”
Section: Resultssupporting
confidence: 74%
“…42 This was also observed to be the case for PEG/PLA nanoparticles made from grafted copolymers, as shown by Banquy et al 13 At higher temperatures, increased disruption of the hydrogen bonding between PEG and water would further contribute to agglomeration. 42 This was also observed to be the case for PEG/PLA nanoparticles made from grafted copolymers, as shown by Banquy et al 13 At higher temperatures, increased disruption of the hydrogen bonding between PEG and water would further contribute to agglomeration.…”
Section: Colloidal Stabilitymentioning
confidence: 55%
See 2 more Smart Citations
“…Due to their intrinsic amphiphilic balance, PEGylated block copolymers are perfect candidates to be formulated into NPs via simple nanoprecipitation techniques. In this regard, previous studies have demonstrated that the amphiphilic balance of the copolymers can impact the size, stability, surface charge, and protein corona formation on the final NPs . However, there are a series of physicochemical parameters that drive the nucleation, growth, and aggregation of the polymers into NPs during the nanoprecipitation process that have not yet been fully understood .…”
Section: Introductionmentioning
confidence: 99%